2014
DOI: 10.1128/aac.02640-14
|View full text |Cite
|
Sign up to set email alerts
|

Pantothenic Acid Biosynthesis in the Parasite Toxoplasma gondii: a Target for Chemotherapy

Abstract: c Toxoplasma gondii is a major food pathogen and neglected parasitic infection that causes eye disease, birth defects, and fetal abortion and plays a role as an opportunistic infection in AIDS. In this study, we investigated pantothenic acid (vitamin B 5 ) biosynthesis in T. gondii. Genes encoding the full repertoire of enzymes for pantothenate synthesis and subsequent metabolism to coenzyme A were identified and are expressed in T. gondii. A panel of inhibitors developed to target Mycobacterium tuberculosis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 50 publications
0
13
2
Order By: Relevance
“…In plants, fungi, and bacteria, pantothenate is synthesized de novo from pyruvate via a conserved three-enzyme pathway; 133 however, animals must acquire pantothenate through their diet or from gastrointestinal bacteria. By searching the T. gondii genome for orthologs of the pantothenate synthesis pathway, Mageed et al 134 identified three conserved genes coding for de novo pantothenate biosynthesis in T. gondii . Among these genes is the terminal enzyme in the pathway, pantothenate synthetase that converts pantoate to pantothenate.…”
Section: Pantothenate Synthetase Inhibitorsmentioning
confidence: 99%
“…In plants, fungi, and bacteria, pantothenate is synthesized de novo from pyruvate via a conserved three-enzyme pathway; 133 however, animals must acquire pantothenate through their diet or from gastrointestinal bacteria. By searching the T. gondii genome for orthologs of the pantothenate synthesis pathway, Mageed et al 134 identified three conserved genes coding for de novo pantothenate biosynthesis in T. gondii . Among these genes is the terminal enzyme in the pathway, pantothenate synthetase that converts pantoate to pantothenate.…”
Section: Pantothenate Synthetase Inhibitorsmentioning
confidence: 99%
“…In contrast to these co-factors, tachyzoites appear unable to scavenge pantothenate, a precursor for coenzyme A, in significant amounts. Instead, they possess the entire synthesis machinery for pantothenate 44 and parasite growth is sensitive to its pharmacological inhibition.…”
Section: Ingredients To Make a Tachyzoitementioning
confidence: 99%
“…Interestingly, T. gondii encodes the pathway in two sequences conserved within the coccidians, which include Hammondia, Neospora, Besnoitia, Cyclospora, and Eimeria genera. The PAN synthesis pathway has been partially characterized in T. gondii, and its essentiality has been proposed based on the use of chemical inhibitors (51). However, the tested drugs had been developed for Mycobacterium tuberculosis homologue (panC), and off-target effects cannot be excluded.…”
Section: Vitamin Bmentioning
confidence: 99%